Management of Land and Building Acquisition Taxes to Increase Regional Original Income - Hariadi, Berian; Meilina, Susiyanti (Adabi : Journal of Public Administration and Business, 2025)
This article examines how the Land and Building Acquisition Duty (BPHTB) can be managed to increase Local Own-Source Revenue (PAD) in Lima Puluh Kota Regency, Indonesia. Using a qualitative, phenomenological case study, the research gathered data through observation of service flows, in-depth interviews with revenue officials and taxpayers, and document analysis, triangulated to enhance credibility. The analysis is structured by the Planning–Organizing–Actuating–Controlling (POAC) framework and aligned with public service principles. Findings show that BPHTB has been institutionalized through clear procedures, receipt and verification of SSPD, validation, and issuance of payment codes, yet several constraints persist: under-realization against PAD targets, taxpayer undervaluation of acquisition prices, limited literacy about obligations, and lean staffing for technical verification. Ongoing improvements include periodic data updating, scaled taxpayer socialization, workflow standardization, and integrated supervision. Proposed enhancements involve a lightweight valuation reference database, explicit escalation criteria for outlier cases, and transparent service-time pledges to strengthen trust while preserving speed. The study concludes that disciplined application of POAC, coupled with citizen-centric service design and modest digital support, can raise voluntary compliance and stabilize BPHTB collections without introducing new taxes. Practical implications include prioritizing inter-agency coordination (with land offices and notaries), targeted staff training, and continuous public communication. The article contributes an operational roadmap for districts seeking to translate BPHTB’s legal mandate into sustained PAD growth.